2020
DOI: 10.32996/ijllt.2020.3.7.22
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Written Corrective Feedback: A Literature Review of Sampling and Design Features, Target Structures and Overall Effects

Abstract: Scholars' attention on written corrective feedback especially the direct-indirect dichotomy has been increasing due to inconsistencies in its effects toward L2 learners’ linguistic accuracy. Therefore, this study was performed to provide a literature review of the increasing number of WCF studies that may provide new perspectives for future research on direct-indirect WCF strategies. This study takes a systematic literature approach to synthesize 16 empirical studies that focusing on the effect of direct-indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…With direct WCF, it could help writers to improve their ability to write something so that writers could avoid writing errors following what had been given when getting WCF (Ferris, 1995) because writers obtained information and knowledge that might not have been known before or already known but not implemented properly. In this study, it could be found that students getting direct WCF performed better than students only getting general comments on their writing through the scores at the end of learning because direct WCF reduced writing errors in grammar (Fhaeizdhyall, 2020) and improved students' ability to understand sentences based on lexical or grammatical structures (Ellis, 2009;Firwana, 2011) so that some of the above aspects became a unity that affected each other.…”
Section: Discussionmentioning
confidence: 86%
“…With direct WCF, it could help writers to improve their ability to write something so that writers could avoid writing errors following what had been given when getting WCF (Ferris, 1995) because writers obtained information and knowledge that might not have been known before or already known but not implemented properly. In this study, it could be found that students getting direct WCF performed better than students only getting general comments on their writing through the scores at the end of learning because direct WCF reduced writing errors in grammar (Fhaeizdhyall, 2020) and improved students' ability to understand sentences based on lexical or grammatical structures (Ellis, 2009;Firwana, 2011) so that some of the above aspects became a unity that affected each other.…”
Section: Discussionmentioning
confidence: 86%